1998
DOI: 10.1046/j.1360-0443.1998.931116493.x
|View full text |Cite
|
Sign up to set email alerts
|

Bloodborne viral infection in Irish injecting drug users

Abstract: HIV prevalence has sustained a low level in this population. Interventions which aim to halt transmission of HCV are necessary and will need to target IDU very early in their injecting careers and also those at risk of commencing to inject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…Many of the identified risk factors for hepatitis C infection in this study are similar to those previously reported with duration of injection most often cited [5,6,15,19,[22][23][24][25]. Other often cited risk factors crudely confirmed in our study include sharing needles/syringes and other injection paraphernalia.…”
Section: Discussionsupporting
confidence: 88%
“…Many of the identified risk factors for hepatitis C infection in this study are similar to those previously reported with duration of injection most often cited [5,6,15,19,[22][23][24][25]. Other often cited risk factors crudely confirmed in our study include sharing needles/syringes and other injection paraphernalia.…”
Section: Discussionsupporting
confidence: 88%
“…Hepatitis infections are very common in opioid users [55]. Prevalence estimates of hepatitis C range from 64 to 100% in many cohorts [56,57,58,59,60,61,62].…”
Section: Clinical Correlates Of Aud In Opioid Dependencementioning
confidence: 99%
“…In this context, the association between injection drug use and HCV infection, which has already been established in the general population and among drug addicts, arises as a possible risk factor for HCV infection in HD patients. 2,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] The objective of this study was to describe the prevalence of positive HCV RNA and investigate injection drug use as an emerging risk factor in chronic renal disease patients on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%